Biomarkers for dementia in Latin American countries: Gaps and opportunities. Issue 2 (13th September 2022) - Parra, Mario A.; Orellana, Paulina; Leon, Tomas; Victoria, Cabello G.; Henriquez, Fernando; Gomez, Rodrigo; Avalos, Constanza; Damian, Andres; Slachevsky, Andrea; Ibañez, Agustin; Zetterberg, Henrik; Tijms, Betty M.; et al.
Abstract: Limited knowledge on dementia biomarkers in Latin American and Caribbean (LAC) countries remains a serious barrier. Here, we reported a survey to explore the ongoing work, needs, interests, potential barriers, and opportunities for future studies related to biomarkers. The results show that neuroimaging is the most used biomarker (73%), followed by genetic studies (40%), peripheral fluids biomarkers (31%), and cerebrospinal fluid biomarkers (29%). Regarding barriers in LAC, lack of funding appears to undermine the implementation of biomarkers in clinical or research settings, followed by insufficient infrastructure and training. The survey revealed that despite the above barriers, the region holds a great potential to advance dementia biomarkers research. Considering the unique contributions that LAC could make to this growing field, we highlight the urgent need to expand biomarker research. These insights allowed us to propose an action plan that addresses the recommendations for a biomarker framework recently proposed by regional experts.